A secondary metabolite of Limosilactobacillus reuteri R2lc drives strain-specific pathology in a spontaneous mouse model of multiple sclerosis - Dale Archer; María Elisa Pérez-Muñoz; Stephanie Tollenaar; Simona Veniamin; Naomi Hotte; Christopher C. Cheng; Kristoff Nieves; Jee-Hwan Oh; Lilian Morceli; Susan Muncner; Daniel R. Barreda; Gurumoorthy Krishnamoorthy; et al. (Cell Reports)
Summary: Limosilactobacillus reuteri is an immunomodulatory bacterium enriched in non-industrialized microbiomes, making it a therapeutic candidate for chronic diseases. However, effects of L. reuteri strains in mouse models of multiple sclerosis have been contradictory. Here, we show that treatment of spontaneous relapsing-remitting experimental autoimmune encephalomyelitis (EAE) mice with L. reuteri R2lc, a strain that activates the aryl hydrocarbon receptor (AhR) through the pks gene cluster, resulted in severe pathology. In contrast, a pks mutant and a pks-negative strain (PB-W1) failed to exacerbate EAE and exhibited reduced pathology compared to R2lc despite earlier disease onset in PB-W1 mice. Differences in pathology occurred in parallel with a pks-dependent downregulation of AhR-related genes, reduced occludin expression in the forebrain, and altered concentrations of immune cells. This work establishes a molecular foundation for strain-specific effects on autoimmunity, which has implications for our understanding of how microbes contribute to chronic conditions and the selection of microbial therapeutics.